Factors influencing results and complications in proximal periprosthetic femoral fractures: a retrospective study at 1- to 8-year follow-up. - Concina, Chiara; Crucil, Marina; Gherlinzoni, Franco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Proximal periprosthetic femoral fractures (PPFFs) are gradually increasing and surgical management is often associated to high risk of complications, due to elderly population and associated comorbidities. We retrospectively assessed 79 patients at 1- to 8-years follow-up, focusing on factors that may have affected results and complications. Methods: Seventy-nine PPFFs were classified according to Vancouver classification in: 4 type B1, 22 type B2, 29 type B3, 24 type C. The average age of the patients was 81.5 year-old (61-95). 37 PPFFs (12 type B2 and 25 type B3) were treated with uncemented tapered fluted revision stems (Link MP Recostruction Stem, Waldermar Link GmbH) and 42 patients with open reduction and internal fixation (ORIF). Patients were clinically and radiographically assessed at a mean 5-year follow-up (1-8 years). Elixhauser Comorbidity index was analysed. Results: All PPFFs, except two, healed within 10 months. Harris Hip score at follow-up was 65.6 in ORIF group and 79.8 in revision hip group (p<0.05). 35.7% and 32.4% had blood transfusions in ORIF and revision hip group respectively (p> 0.05). 5 patients in ORIF group and 2 patients in revision hip group died within 12 months from surgery (p<0.05). Conclusions: Both ORIF and hip revision arthroplasty with modular uncemented tapered fluted stems are valid procedures for Vancouver B2 and B3 PPFFs. Restricted weight-bearing, high number of comorbidities with elevated Elixhauser Comorbidity Index and ORIF are associated to high 12-month mortality.